Investigating health related fitness level among down syndrome in Kelantan - Zhen, Lee Wan (2018)
Down syndrome (DS) is a category of intellectual disabilities which is associated with abnormalities in chromosome 21. Individuals with DS have lower physical fitness levels compared to their typical peers. Furthermore, research also states that their level of physical fitness are generally lower than individuals with intellectual disabilities from other categories. The low level of physical fitness may affect their health and may negative affect their quality of life. This study was conducted to investigate the fitness level among Down syndrome in Kelantan. There were 16 Down syndrome participants from Community Based Rehabilititation (CBR) and Kelantan Down Syndrome Association (PSDNK) participated in this study. The physical fitness levels such as body mass index, body fat percentage, Rockport 1-mile walking test, sit-up test, curl up test, hand grip test as well as sit-and-reach test have been conducted. The study found that the health related physical fitness levels of DS was low, conversely, the body mass index and body fat percentage are high. These findings indicating that the health related fitness of DS in this study are not healthy. Therefore, it is imperative for the DS to actively participate in physical activities in order to reduce the risk of having non-communicable diseases (NCD) such as diabetes, hypertension or heart diseases.